2020
DOI: 10.1042/bsr20192770
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA in blood products and its potential effects on transfusion

Abstract: Blood transfusions are sometimes necessary after a high loss of blood due to injury or surgery. Some people need regular transfusions due to medical conditions such as haemophilia or cancer. Studies have suggested that extracellular DNA including mitochondrial DNA present in the extracellular milieu of transfused blood products has biological actions that are capable of activating the innate immune systems and potentially contribute to some adverse reactions in transfusion. From the present work, it becomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 113 publications
(167 reference statements)
0
8
0
Order By: Relevance
“…PCs also contain mtDNA, which has been linked to transfusion reactions. 49,[96][97][98] In fact, Boudreau et al showed that activated platelets release mitochondria, both in encapsulated microparticles and as free organelles. The levels of extracellular mitochondria found in transfused PCs are higher in those having caused transfusion reactions (FNHTR cutaneous and cardiovascular symptoms) in transfusion patients.…”
Section: Pc Preparation and Storage Lesions Promote Secretion Of Biolmentioning
confidence: 99%
“…PCs also contain mtDNA, which has been linked to transfusion reactions. 49,[96][97][98] In fact, Boudreau et al showed that activated platelets release mitochondria, both in encapsulated microparticles and as free organelles. The levels of extracellular mitochondria found in transfused PCs are higher in those having caused transfusion reactions (FNHTR cutaneous and cardiovascular symptoms) in transfusion patients.…”
Section: Pc Preparation and Storage Lesions Promote Secretion Of Biolmentioning
confidence: 99%
“…From this study, we used 2-3 drops of blood sample or about 300 μ l. Normally, the amount of DNA from whole blood per ml is about 260–1,474 ng/ml [ 9 ] or 1,700 leucocyte-eq/ml [ 10 ]. Therefore, the 300 μ l of blood sample which used in this experiment is equal to 78–441 ng of DNA or 510 leucocytes.…”
Section: Discussionmentioning
confidence: 99%
“…While thorough investigation is lacking, some reports have indicated that cfDNA may have potential use in (i) biobanking; analysis of cfDNA in cord blood plasma has been useful for sample identification [ 115 ], (ii) forensic casework; cfDNA has been genetically profiled in samples recovered from externally found body fluids, such as blood, sweat, and feces [ 116 , 117 , 118 , 119 ], and (iii) quality control assurance of blood donations [ 120 ] or transfusions [ 121 ].…”
Section: Sequence Analysis Of Cfdnamentioning
confidence: 99%